Molecular Docking Simulation of Anti-tumor Necrosis Factor Alpha from Hemp Seed (Cannabis sativa L.) - Racha, Satapat; Racha, Kannika; Hirattanapun, Ekkapon (YRU Journal of Science and Technology, 2020)
A pro-cytokine tumor necrosis factor alpha (TNF-alpha), is a novel potential target for treatment and prevention of immune-mediated inflammation. Potential anti-inflammatory activity of phenolamides from hemp seed have been reported, but the mechanism of action is unclear. Main aim of the study was to investigate the molecular interaction between five phenolamides and TNF-alpha by molecular docking. The results showed that coumaroylaminobutanol glucopyranoside is the most promising inhibitor of TNF-alpha. This finding provides a better understanding of the molecular basis for the anti-inflammatory activity of hemp seed.